2020
DOI: 10.1057/s41272-020-00236-4
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable machine learning for demand modeling with high-dimensional data using Gradient Boosting Machines and Shapley values

Abstract: Forecasting demand and understanding sales drivers are one of the most important tasks in retail analytics. However, traditionally, linear models and/or models with a small number of predictors have been predominantly used in sales modeling. Taking into account that real-world demand is naturally determined by complex substitution and complementation patterns among a large number of interrelated SKUs, nonlinear effects of prices, promotions, seasonality, as well as many other factors, their lagged values, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…2 Feature influence to the counterpressing prediction based on SHAP-values method to identify the individualized feature contribution to machine learning models. This method has been effectively used in different applications (Antipov et al 2020;Meng et al 2020;Ibrahim et al 2020;Anzer and Bauer 2021).…”
Section: Detection Of Counterpressingmentioning
confidence: 99%
“…2 Feature influence to the counterpressing prediction based on SHAP-values method to identify the individualized feature contribution to machine learning models. This method has been effectively used in different applications (Antipov et al 2020;Meng et al 2020;Ibrahim et al 2020;Anzer and Bauer 2021).…”
Section: Detection Of Counterpressingmentioning
confidence: 99%
“…Another study from Bangladesh reported the highest accuracy when using an artificial neural network [ 10 ]. We may attribute the observed superiority of the XGBoost to its ability to leverage the outputs of weak sequential decision trees, where each new tree builds on the weaknesses of the previous trees to make accurate predictions and its ability to effectively handling complex, high-dimensional data for classification [ 27 ]. The SVM models followed the XGBoost model with regards to discrimination under the ROC curves in all the three undernutrition indicators.…”
Section: Discussionmentioning
confidence: 99%
“…But interpretability has been a key area in the new wave of ML research and much progress has been made in recent years. Antipov and Pokryshevskaya (2020) applied a recently developed unified approach to interpreting model predictions called Shapley Additive Explanations. They showed that the Shapley additive explanation of boosting tree predictions are very insightful, uncovering the effects of prices and promotions, as well as ideas related to stockpiling and cross-product effects.…”
Section: Methodological Developmentsmentioning
confidence: 99%